1988
DOI: 10.1099/0022-1317-69-7-1617
|View full text |Cite
|
Sign up to set email alerts
|

Inapparent Virus Infections and their Interactions in Pupae of the Honey Bee (Apis mellifera Linnaeus) in Australia

Abstract: SUMMARYWhen honey bee pupae from seemingly healthy Australian colonies were injected with various salt solutions, inapparent infections of black queen-cell virus (BQCV), Kashmir bee virus (KBV), sacbrood virus (SBV) and, occasionally, cricket paralysis virus were activated. The activated viruses replicated to detectable concentrations after pupae were incubated at 35 °C for 3 days. Inapparent infections of SBV, but not the other viruses, were also activated merely by incubating pupae at 35 °C. The replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
85
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 16 publications
9
85
1
1
Order By: Relevance
“…Second, the mite can also trigger virus replication by a simple mechanical effect, cuticle piercing, or by injection of external proteins into the insect hemolymph (18). The latter hypothesis is supported by several studies that demonstrated that there was reactivation of viruses already present in the insect following experimental inoculation (3,17). However, the association between parasitic mite syndrome and viruses is still controversial (21).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Second, the mite can also trigger virus replication by a simple mechanical effect, cuticle piercing, or by injection of external proteins into the insect hemolymph (18). The latter hypothesis is supported by several studies that demonstrated that there was reactivation of viruses already present in the insect following experimental inoculation (3,17). However, the association between parasitic mite syndrome and viruses is still controversial (21).…”
mentioning
confidence: 67%
“…Two of these viruses, SBV and CBPV, produce clinical signs that are clearly identifiable by beekeepers, whereas the majority of the viruses are believed to cause persistent, usually inapparent infections in honey bees (3,6,17,20), and their associations with colony mortality remain unexplained (10,25).…”
mentioning
confidence: 99%
“…Although virus coinfections have long been recognized in plants and other animals, information on mixed virus infections in honey bees has accumulated very slowly over the last decade. Anderson and Gibbs (1988) first reported infections of KBV, SBV, and BQCV in bee colonies and demonstrated that replication of SBV and BQCV could be suppressed by activation of KBV. The genetic study of Evans (2001) showed that KBV and ABPV could infect the same bee, simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, attempts to determine the frequency of viruses in the field have been slowed by the fact that bee colonies can be attacked by more than one virus. Multiple viral infections have been reported in bees by a number of authors including Anderson (1990), Anderson and Gibbs (1988), Benjeddou et al (2001), Evans (2001), Hung et al (1996a,b), and Leat et al (2000). For many years, detection and identification of viral infection in honey bee colonies were based largely on serological methods like Ouchterlony gel diffusion, indirect fluorescent antibody (IFA) and enzyme-linked immunosorbent assay (ELISA) tests (Allen and Ball, 1995;Allen et al, 1986;Anderson, 1984).…”
mentioning
confidence: 99%
“…Bee colonies can harbour viruses without showing obvious disease symptoms (Anderson and Gibbs, 1988;Dall, 1985;Gauthier et al, 2007). Different approaches have been used to clarify the role of viruses in bee colonies.…”
mentioning
confidence: 99%